A clinical screening tool to detect genetic cancer predisposition in pediatric oncology shows high sensitivity but can miss a substantial percentage of affected children - Friedrich, Ulrike A.; Bienias, Marc; Zinke, Claudia; Prazenicova, Maria; Lohse, Judith; Jahn, Arne; Menzel, Maria; Langanke, Jonas; Walter, Carolin; Wagener, Rabea; Brozou, Triantafyllia; Varghese, Julian; et al. (Genetics in medicine, 2023)
Purpose - Clinical checklists are the standard of care to determine whether a child with cancer shows indications for genetic testing. Nevertheless, the efficacy of these tests to reliably detect genetic cancer predisposition in children with cancer is still insufficiently investigated. - Methods - We assessed the validity of clinically recognizable signs to identify cancer predisposition by correlating a state-of-the-art clinical checklist to the corresponding exome sequencing analysis in an unselected single-center cohort of 139 child-parent data sets. - Results - In total, one-third of patients had a clinical indication for genetic testing according to current recommendations, and 10.1% (14 of 139) of children harbored a cancer predisposition. Of these, 71.4% (10 of 14) were identified through the clinical checklist. In addition, >2 clinical findings in the checklist increased the likelihood to identifying genetic predisposition from 12.5% to 50%. Furthermore, our data revealed a high rate of genetic predisposition (40%, 4 of 10) in myelodysplastic syndrome cases, while no (likely) pathogenic variants were identified in the sarcoma and lymphoma group. - Conclusion - In summary, our data show high checklist sensitivity, particularly in identifying childhood cancer predisposition syndromes. Nevertheless, the checklist used here also missed 29% of children with a cancer predisposition, highlighting the drawbacks of sole clinical evaluation and underlining the need for routine germline sequencing in pediatric oncology.